Expansion of Distance Education in higher education: Trajectories in Argentina, Brazil, Chile and Colombia - JANAINA KUNZLER; Artur Jacobus; João Batista Storck; Maria Aparecida Marques da Rocha (Universidade do Minho, 2022)
During the first two decades of the 21st century, higher education has had an accentuated expansion in South America. To be able to handle this increase in demand, international organizations have encouraged the region's countries to turn to distance education. Therefore, it is important to understand how this mode of education has been incorporated into higher education policies in different South American countries. The aim of this article is to compare the reality of four South American countries with respect to the level of participation in distance education in higher education, namely in Argentina, Brazil, Chile and Colombia. Regarding the methodology, we analyzed official and research data about the latest evolution of distance education in higher education in the four countries studied. The analysis reveals that distance education has experienced a significant expansion in these countries since 2010, with the greatest increase occurring in Brazil. We concluded that, despite external factors in favor of distance education, internal environments in each country influence the manner and tempo with which this pressure is reflected in their respective higher education policies.